2006
DOI: 10.1007/s00125-006-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal permeability precedes clinical onset of type 1 diabetes

Abstract: Aims/hypothesis Recent observations have shown subclinical intestinal abnormalities in human type 1 diabetes. Whether these are related to the pathogenetic process or secondary to the diabetes remains to be clarified. The aim of this study was to investigate this issue by examining intestinal permeability to sugars in subjects at different stages of type 1 diabetes: preclinical, new-onset and longterm established disease. Methods Eighty-one subjects with islet autoimmunity (18 preclinical, 28 new-onset and 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
259
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(282 citation statements)
references
References 10 publications
(16 reference statements)
12
259
1
10
Order By: Relevance
“…Although there are no definitive clinical studies linking enteric bacterial infections to the development of human type 1 diabetes, there are a growing number of reports of type 1 diabetes patients who concomitantly present with intestinal enteropathies [8][9][10][11][12]35]. Our results demonstrate that intestinal barrier dysfunction, in this case mediated by the enteric bacterial pathogen, C. rodentium, is a catalyst for the accelerated development of insulitis and for the priming of CD8 + T cells that are potentially diabetogenic.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Although there are no definitive clinical studies linking enteric bacterial infections to the development of human type 1 diabetes, there are a growing number of reports of type 1 diabetes patients who concomitantly present with intestinal enteropathies [8][9][10][11][12]35]. Our results demonstrate that intestinal barrier dysfunction, in this case mediated by the enteric bacterial pathogen, C. rodentium, is a catalyst for the accelerated development of insulitis and for the priming of CD8 + T cells that are potentially diabetogenic.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, viral infections are associated with the onset of type 1 diabetes (particularly enteroviruses and rotaviruses) and also affect gut permeability [33,34]. Reports have shown that children with type 1 diabetes have increased barrier defects in their small intestines ( [8] and reviewed in [35]) and have a higher incidence of enteroviral infections [36]. Moreover, recent studies have also implicated innate recognition of enteric commensal microbes in the modulation of diabetes suffered by NOD mice [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In autoimmune diabetes, the lymphocytes in the inflamed islets show mucosal homing properties as demonstrated both in animal models and human T1D (13)(14)(15). Also, the aberrancies of the gut immune system, such as subclinical intestinal inflammation (16,17) and increased gut permeability (18,19), have been associated with human T1D. Accordingly, the upregulation of IL-17 immunity may be a marker of altered mucosal immune response in T1D.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, intestinal mucosa from individuals at risk for T1D or with T1D exhibit abnormalities in intestinal permeability as evaluated by functional tests or electron microscopy studies. [22][23][24] In experimentally induced diabetes in rats or mice, changes in intestinal permeability are also detected before the onset of diabetes; increased intestinal permeability in these cases has been shown to be dependent on increased zonulin expression, which regulates tight junctions in the intestinal mucosa. [25][26][27] Additionally, mucosal biopsy, fecal microbiota and serological studies have indicated that the composition of intestinal microbiota may influence the immune mechanisms that participate in the development of CD 28,29 and T1D.…”
Section: Introductionmentioning
confidence: 99%